Dairy industry derived wastewater treatment sludge: Generation, type and characterization of nutrients and metals for agricultural reuse. (1st September 2019) - Ashekuzzaman, S.M.; Forrestal, Patrick; Richards, Karl; Fenton, Owen
Abstract: Globally, the processing of milk and dairy products leads to huge volumes of dairy processing wastewater treated sludge. Currently, there are knowledge gaps relating to the volumes generated and the nutrient and metal contents of these sludges. This lack of knowledge prevents the dairy processing industry from making informed pre and post waste generation decisions. Using Ireland as a case study volumes generated are estimated (2012–2017) and a two year seasonal database (2016–2018) across four sludge types (bio-chemically treated activated sludge; lime treated dissolved air flotation processing sludge; a combined treatment sludge and anaerobically digested sludge) utilising samples from nine dairy processing plants was created. Results show that dairy processing sludge increased by 39% in the period up to 126, 718 tonnes (wet weight). Database results showed that nutrient contents did not vary seasonally but varied significantly across sludge type and processing plants. The median values (g kg −1 dry weight) for N:P:K for the four sludge types were N: 57.2, 19.5, 46 and 70.4, P: 36.8, 65.9, 20 and 14.6, and K: 7.2, 3.9, 2.9 and 6.1, respectively. Heavy metal concentrations across all samples were significantly lower than those regulated by the European Union for controlling metals accumulation in agricultural land due to sludge recycling. The characterization profile presented in this paper serves as a national and international reference database for future investigations that focus on the valorisation of dairy processing sludge. Graphical abstract: Image 1 Highlights: Dairy processing sludge streams were characterised for nutrients and metals. Sample characteristics varied in respect to the wastewater treatment process. N, P concentrations were higher in dairy sludge than in common organic fertiliser. Samples showed very low heavy metal concentrations comparing the EU guideline. Results showed high potential for nutrient recovery and agricultural recycling.